Experience in the management of a severe burn patient with multiple complications. Issue 1 (2018) - L, Xu-sheng; Y, Ji-chao; Q, Hua-bing; G, Weidong; Y, Hong; L, Qi-zhi; T, Li-ju; H, Xian-hui
No abstract available